GLOBAL CLINICAL PRACTICE AND PERSONALIZED CHOICES FOR ORAL ANTICOAGULANT THERAPY FOR NON-VALVULAR ATRIAL FIBRILLATION - A. V. Fonyakin (Nevrologiâ, Nejropsihiatriâ, Psihosomatika, 2016)
The possibilities of antithrombotic therapy to prevent thromboembolic events in non-valvular atrial fibrillation (AF) have substantially expanded after the design and clinical introduction of direct oral anticoagulants (DOACs). The start of clinical use of these agents has opened a new page in oral anticoagulant therapy for the prevention of thromboembolic events in AF. Dabigatran etexilate is the first DOAC that underwent clinical trial registration 6 years ago. After completion of the RE-LY  trial, the positive safety and efficacy profile of dabigatran has been confirmed over the last 6 years of its clinical use in actual practice in more than 250 thousand patients in nearly 100 countries around the world. The risk of ischemic stroke, intracranial and intracerebral hemorrhages, and death was shown to be simultaneously statistically significantly lower only in the dabigatran 150 mg group than in the warfarin group. The rate of major bleeding and all bleedings requiring hospitalization and that of myocardial infarction were comparable. Massive gastrointestinal bleeding (GIB) was more commonly recorded in the patients taking dabigatran; the RE-LY  trial investigating the reduced dabigatran dose used in Europe and Russia has shown that it may be used in a group of patients at higher bleeding risk.The results of the investigation in the Medicare system have indicated that treatment with dabigatran 150 mg versus rivaroxaban reduces the risk of intracranial hemorrhage by 40%, major hemorrhage by 33%, and massive GIB by 39%. Thus, dabigatran demonstrates a favorable benefit-risk ratio in real world practice and requires no additional modifications in the current instruction and recommendations for its use.